PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS KURIKULUM 2013 PADA MATERI PROTISTA KELAS X SMA - Suryawati, Evi Suryawati; Sayuti, Irda Sayuti; ', Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to developed of biology learning device based curriculum 2013 on the topics of protists grade X senior high school. Learning device includes syllabus, lesson plan (RPP), student worksheet (LKS), authentic assessment, and learning media. Research conducted at the Campus Biology Education FKIP Riau University and a limited trial at SMAN Plus Riau Province on March – June 2015. The research used development research approach with ADDIE and through limited trial. Subjects this research consist of Basic Competence 3.5 and Basic Competence 4.5. The data collection instruments used were a validation sheet. Validation sheet assessed by internal and external validation. Validation sheet is filled for each learning device developed. The collected data were analyzed as descriptive statiscally. The average results of the validity of the learning device are 3.5 for lesson plan, 3.4 for student worksheet, 3.4 for written assessment, 3.4 for attitude assessment, 3.5 for performance assessment, 3.5 for product assessment, 3.5 for project assessment, 3.6 for self-assessment, 3.5 for portfolio assessment and 3.3 for learning media. Next step is limited trial using a questionnaires student worksheet, a written test questions, and self-assessment are tried on class X MS3 SMAN Plus Riau Province with 24 students. From the results of the validation can be concluded that the development of the curriculum-based learning biology in 2013 on the topic protists can already be implemented through field trials. Key words: development, learning device, curriculum 2013, biology